Physicochemical Characteristics of Edible Film Sodium Caseinate with Sappan Wood Extract Addition - Govinda Anggita Fortin; Yohana Sutiknyawati Kusuma Dewi; Lucky Hartanti (University of Sultan Ageng Tirtayasa, 2023)
Packaging will protect food from physical and chemical deterioration and maintains the economic value during storage. Generally, food packaging was made by plastic material which is cheap and easy to use. Plastic waste makes it difficult to degrade, so it is necessary to develop technology that aims to reduce the impact of plastic waste pollution by biodegradable packaging included edible film. Casein is one of the hydrocolloid ingredients which is utilized to made of edible film. Casein has flexibility, transparency, and tasteless film properties also it has a carrier antioxidant capacity. The addition of sappan wood extracts to the edible film that is interesting to observed as a carrier of antioxidant compounds. This research was conducted to obtain the concentration of sappan wood extract, which produces the best physicochemical characteristics of sodium caseinate edible film. The method used in this study was a one-factor Randomized Block Design (RBD) consisting of 5 levels of sappan wood extracts (0%, 2.5%, 5%, 7.5%, and 10% w/vtotal) with 5 replications. Based on this research to obtained the best physicochemical characteristics of edible film sodium caseinate with the addition 10% sappan wood extracts, which has a thickness value of 0.20 mm, solubility 24.421%, color L* (79.0) a* (8.3) b* (32.8), water holding capacity of 6.863 (g/g), and antioxidant activity of 24.170%.